Cardiac Myxomas - Symptomology, Investigations and Surgical Treatment - Single Centre Experience of Fifteen Years at Grant Medical College, Mumbai, Maharashtra - Suraj Wasudeo Nagre; Krishnarao N Bhosle (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2018)
Introduction: The aim of study is to describe the clinical symptoms, investigation findings and surgical treatment of cardiac myxomas. Method: From May 2002 to May 2017, 50 patients of primary or recurrent intracardiac myxoma underwent surgical excision at our institute. Their age ranged from 25 years to 55 years. Out of which 20 males and 30 females. Commonest presenting symptoms are dyspnea and palpitation. 35 Left atrial, 13 Right atrial, one right ventricular and one left ventricular myxoma.